Low-Cost Strategy Implementation in the Turkish Airline Industry Compared to the Pioneer Low-Cost Carrier in the United States - Kuran, B (2017)
This paper is a qualitative research about the low-cost strategy implementation in the Turkish airline industry based on the country`s only low-cost carrier. In order to understand how the company implements low-cost strategy, in-detail literature review on strategy evolution, industry background, and the birth of low-cost airline model are provided. The pioneer low-cost airline company in the United States is also analysed to compare and contrast the strategy implementation of the focused company in Turkey. How the strategy is implemented in Turkey and why it is implemented by only one company are the main questions to be answered in this paper. The key feature of this study is to rely on empirical data from natural and social world, and connect them to the concepts mentioned in the literature review to discuss the relationship between the theory and practice. Research findings seek to contribute to the knowledge in strategic management in that context.